IMPLEMENTASI K-NEAREST NEIGHBOR UNTUK MENENTUKAN PREDIKSI PENJUALAN: (STUDI KASUS : PT MAKSIPLUS UTAMA INDONESIA) - Rini Nuraini Sukmana; Abdurrahman Abdurrahman; Yohanes Wicaksono (JURTIK:Jurnal Penelitian dan Pengembangan Teknologi Informasi dan Komunikasi, 2020)
Maksiplus Utama Indonesia is an MLM based company that produces and sells fertilizers. Maksiplus has many products spread in Indonesia. From some of these products sometimes there are some whose sales results are not as expected, and cause a lack of company profits. Management sometimes feels difficulty in determining whether product sales will rise or not. To help predict sales, a method that is able to provide alternative solutions is needed. The method used in this sales prediction is K-Nearest Neighbor. The system output is presented in the form of the calculation results from the K-Nearest Neighbor method. The results to be achieved in this study are companies can be helped in making decisions. From the output of the system in the form of numbers, it is expected to be easily understood and used as material for consideration by management in determining whether a product's sales will rise or not. Keywords: sales predictions, K-Nearest Neighbor, Maksiplus.